Tuning magnetic properties based on FeCoNiSi0.4Al0.4 with dual-phase nano-crystal and nano-amorphous microstructure. (February 2020) - Zhang, Bin; Duan, Yuping; Yang, Xuan; Ma, Guojia; Wang, Tongmin; Dong, Xinglong; Zeng, yuansong
Abstract: The idea of adjusting the crystallinity of powders via controlling the phase composition of milling precursor (ribbons) has been used to prepare FeCoNiSi0.4 Al0.4 high entropy alloy powders (HEAPs) with dual-phase nano-crystal (NC) and nano-amorphous (NA) microstructure. The crystallinity of HEAPs are related to the FCC phase proportion of milling precursor: within 60%, positive correlation; beyond 60%, negative correlation. Different phase structure for ribbons can be obtained by taking advantage of the difference in phase stability, as an extension of annealing time induces the increment of FCC phase content. The introduction of nano-scale phase separation in HEA ribbons provides a prerequisite. Multiphase NCs distribute randomly in matrix, while NCs with FCC phase are aggregated into about 50 nm regions embedded in matrix. Three kinds of phase transition are co-existed during the dry-milling process, generating the coexistence of NCs and NAs. Due to the unique microstructure, in especial NCs doped by NAs, and the skillful preparation technology, a small H c, varying from 12.97 Oe (C0 ) to 28.33 Oe (C50 ), and a large complex permeability ( μ′ ), varying from 2.60 (C0 ) to 2.30 (C50 ), can be obtained. Highlights: As-cast dry-milling technology has been designed to prepare HEAPs. The crystallinity of powders under the same composition can be tuned. The phase proportion of ribbons can be controlled by annealing time. Nanocrystal and nanoglass microstructure can be obtained. Magnetic properties can be changed by crystallinity.